2000
DOI: 10.1093/clinchem/46.8.1136
|View full text |Cite
|
Sign up to set email alerts
|

Space Flight Is Associated with Rapid Decreases of Undercarboxylated Osteocalcin and Increases of Markers of Bone Resorption without Changes in Their Circadian Variation: Observations in Two Cosmonauts

Abstract: Background: Microgravity induces bone loss by mechanism(s) that remain largely unknown. Methods: We measured biochemical markers related to bone remodeling in two cosmonauts before, during, and after 21- and 180-day space flights, respectively. Results: During both flights, type I procollagen propeptide and bone alkaline phosphatase decreased as early as 8 days after launch. Undercarboxylated osteocalcin percentage increased early and remained high during both flights. Vitamin K s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 15 publications
5
49
0
1
Order By: Relevance
“…(Bottom) Significant calcium kinetic study findings: intake ( ), absorption (+), and resorption (×). The x-axis labels match the collection profiles for the blood data; the only difference for urine data was that these were completed at R + 5-9 (instead of 5-10) and R + 10-16 days (instead of [11][12][13][14][15][16][17].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bottom) Significant calcium kinetic study findings: intake ( ), absorption (+), and resorption (×). The x-axis labels match the collection profiles for the blood data; the only difference for urine data was that these were completed at R + 5-9 (instead of 5-10) and R + 10-16 days (instead of [11][12][13][14][15][16][17].…”
Section: Figmentioning
confidence: 99%
“…Effective countermeasures that reduce bone loss will not only help ensure the health and safety of crews on shorter missions (such as those used for the International Space Station) but will also contribute to the development of treatments for bone diseases on Earth. (1,11,12) Bone resorption, assessed by measuring urinary concentrations of collagen cross-links (7,(13)(14)(15)(16) or hydroxyproline, (6,17) is greater during space flight than before flight. Initial calcium tracer kinetic studies conducted on Mir also indicated that bone resorption increases during flight, (7) despite use of exercise countermeasures.…”
Section: Introductionmentioning
confidence: 99%
“…135 Vitamin K metabolism and action may also be affected in microgravity. 136 Riepl et al 137 observed altered levels of several gastroenteropancreatic peptides during both the initial phase of exposure and after 4 weeks of space flight. Maccarrone et al 138,139 observed that the catalytic efficiency and affinity of soybean lipooxygenase-I (LOX-1) on linoleic acid was four times higher in flight than on ground.…”
Section: Enzymes and Metabolismmentioning
confidence: 99%
“…(3)(4)(5) Studies also showed that crewmembers during spaceflight experienced reduced bone formation, augmented bone resorption, and persistently higher fracture risk even 1 year after returning to Earth. (6,7) Similarly, mechanical unloading also led to significant BMD decrease and concomitant higher incidence of bone fractures for patients with long-term bed rest or immobilization. (8,9) In view of the side effects or high cost of antiosteoporosis drugs (eg, calcitonin, hormones, and calcium and vitamin D preparations), (10)(11)(12)(13)(14) safe and noninvasive biophysical countermeasures for disuse osteoporosis might be more promising in clinical application, and especially favorable for the use of spaceflight.…”
Section: Introductionmentioning
confidence: 99%